Precision Surface Grinding of Silicon Carbide - Mohamed Konneh (International Journal of Engineering Materials and Manufacture, 2016)
Silicon carbide (SiC) is well known for its excellent material properties, high durability, high wear resistance, light weight and extreme hardness. Among the engineering applications of this material, it is an excellent candidate for optic mirrors used in an Airbone Laser (ABL) device. However, the low fracture toughness and extreme brittleness characteristics of SiC are predominant factors for its poor machinability. This paper presents surface grinding of SiC using diamond cup wheels to assess the performance of diamond grits with respect to the roughness produced on the machined surfaces and also the morphology of the ground work-piece. Resin bonded diamond cup wheels of grit sizes 46 µm, 76 µm and 107 µm; depth of cut of 10 µm, 20 µm and 30 µm; and feed rate of 2 mm/min, 12 mm/min and 22 mm/min were used during this machining investigation. It has been observed that the 76 grit performs better in terms of low surface roughness value and morphology.